A novel DOPO‐containing HTBN endowing waterborne polyurethane with excellent flame retardance and mechanical properties. Issue 44 (7th May 2020) - Wang, Hui; Wang, Shuang; Du, Xiaosheng; Du, Zongliang; Wang, Haibo; Cheng, Xu
Abstract: A novel flame‐retardant DHTBN (hydroxyl‐terminated polybutadiene acrylonitrile modified with DOPO) with phosphorus‐containing pendant groups is synthesized based on addition reaction between the hydroxyl‐terminated polybutadiene acrylonitrile and DOPO, which is followed to prepare flame‐retarded WPU (FR‐WPU). The chemical structures of DHTBN and FR‐WPU are confirmed via 31 P NMR, XPS, and FT‐IR. The mechanical properties, thermal stability, and flame retardancy of FR‐WPU are conducted a series of tests. The tensile strength and elongation at break for the FR‐WPU films first increased and then decreased with increasing of DOPO contents. The results show that the incorporation of DHTBN into the WPU backbone slightly reduces the thermal stability of FR‐WPU. However, the incorporation of DHTBN into WPU improves the flame retardancy. The TGA‐FIR and Py‐GC‐MS results indicate the gas phase flame‐retardant effect of DHTBN. Furthermore, the morphology, elemental composition, and content of residual char from the FR‐WPU exhibited condensed‐phase flame‐retardant effects on the WPU films. Abstract :